TANGGUL SUNGAI SERAYU HILIR DARI MUARA HINGGA BENDUNG GERAK SERAYU - Riade Yusuf Hernanda; Robert M. Nainggolan; Suseno Darsono; Dwi Kurniani (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
Flood is a condition where water is overflowing in the discharge channel (river) caused by the inability of the cross section of the river in accommodating the flood discharge. Serayu river always brings floods every year, especially in the area of Banyumas and Cilacap. Flood debit plan used in the analysis of a cross section of Serayu river from the moving weir Serayu to estuary in Cilacap uses a return period of 50 years. Flood debit plan was analyzed by using SCS-CN method (Soil Conservation Service - Curve Number) with the help of software HEC-HMS. From the analysis of flood debit value of the plan, namely: Junction 12 amounted to 2088.4 m3/second, the junction 13 at 2417.1 m3 second, and 15th junction of 1386.9 m3/second. Existing cross-sectional analysis of Serayu river was done by using HEC-RAS software. The output of the HEC-RAS software is used to determine the location of planning the embankment, which is in areas experiencing river water overflowing. Central Java Serayu Downstream Embankment planning will be done with an estimated construction cost of Rp. 63,131,000,000.00 (sixty three billion one hundred and thirty one million rupiah) with a duration of work for 18 weeks.